Biotinidase deficiency: a treatable cause of hereditary spastic paraparesis - Radelfahr, Florentine; Riedhammer, Korbinian M.; Keidel, Leonie F.; Gramer, Gwendolyn; Meitinger, Thomas; Klopstock, Thomas; Wagner, Matias (Neurology. Genetics, 2020)
Objective To expand the genetic spectrum of hereditary spastic paraparesis by a treatable condition and to evaluate the therapeutic effects of biotin supplementation in an adult patient with biotinidase deficiency (BD). - Methods We performed exome sequencing (ES) in a patient with the clinical diagnosis of complex hereditary spastic paraparesis. The patient was examined neurologically, including functional rating scales. We performed ophthalmologic examinations and metabolic testing. - Results A 41-year-old patient presented with slowly progressive lower limb spasticity combined with optic atrophy. He was clinically diagnosed with complex hereditary spastic paraparesis. The initial panel diagnostics did not reveal the disease-causing variant; therefore, ES was performed. ES revealed biallelic pathogenic variants in the BTD gene leading to the genetic diagnosis of BD. BD is an autosomal recessive metabolic disorder causing a broad spectrum of neurologic symptoms, optic atrophy, and dermatologic abnormalities. When treatment is initiated in time, symptoms can be prevented or reversed by biotin supplementation. After diagnosis in our patient, biotin supplementation was started. One year after the onset of therapy, symptoms remained stable with slight improvement of sensory deficits. - Conclusions These findings expand the genetic spectrum of the clinical diagnosis of complex hereditary spastic paraparesis by a treatable disease. Today, most children with BD should have been identified via newborn screening to start biotin supplementation before the onset of symptoms. However, adult patients and those born in countries without newborn screening programs for BD are at risk of being missed. Therapeutic success depends on early diagnosis and presymptomatic treatment.
Gesehen am 10.04.2022